Época de aplicação de herbicidas dessecantes para antecipação da colheita de sementes de feijão carioca - Castoldi, Camile Thaís (2017)
In order to implanta high productive potential in a crop it's necessary to appreciate a highquality seed, which presents high vigor, germination and maximum dry water's accumulation. These characteristics are generally present in weed's physiologic maturity, making it impossible mechanical harvest, because the high plant's humidity. However, later harvests may expose seeds to climate adversities, which may compromise their potential and quality. Thus, pre-harvest desiccations of the bean crop are carried out, aiming at theanticipation of the harvest, but, the used herbicides can cause damage to the seeds. Therefore, this projectaims to evaluatethe effect of desiccations on carioca’s bean seedsusing different herbicides at low doses and different times, and the treatment’s effects about physical, physiologic and sanitary quality of the seeds. For this, the experiment was conducted according to the experimental design of random blocks, in the factorial arrange 2 x 3 x 4 + 1 (application time x herbicides x doses + additional), with four replications. The plants of carioca bean, cultivar Pérola, were desiccated when the seeds had 42 and 30 % water content to the herbicides amonio-glufosinate, saflufenacil and diquat, for 0, 50, 75 and 100 % doses in relation to the recommended dose,which corresponds to 1.9 L ha-1, 105 g ha-1, 1.75 L ha-1, respectively for each of the herbicides. The 0% dose corresponds to the control treatment, without desiccant application and harvested on the same date as the desiccations. The additional treatment, also without desiccant application, was harvested with 18% water content.To verify physiologic, physical and sanitary quality of the seeds, germination, first germination count, germination speed index (IVG), cold test, accelerated aging, seeding length and radicle, matter transfer, thousand grains weight, hectoliter weight, electrical conductivity and sanity test analysis were realized. After analysis and interpreting the results, it was concluded, in general, the use of herbicides for desiccation in carioca beans, aiming the anticipation of the harverst, using the recommended dose of the herbicides amonio-glufosinate, saflufenacil and diquat, did not is recommended, since it causes losses in the quality of bean seeds. However, when the desiccant needs to be applied, it is recommended to use reduced doses, because they have lower losses. Also verified that the harvesting of seeds at water content between 30 and 42 % without use of desiccants, the seeds presents the same characteristics necessary for a good seed performance in the field.